Factors Associated with Giving Formula Milk to Babies Aged Between 0-6 Months - Fanimah Hi Yusup; Sulistiyah Sulistiyah; Tut Rayani Aksohini Wijayanti (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Low exclusive breastfeeding rates are often linked to the widespread use of formula milk in infants. Formula feeding cannot replace colostrum, the first milk produced after birth, which is crucial for providing infants with essential nutrients and immunity. Without colostrum, infants are at increased risk of developing diarrhea, septicemia, meningitis, and other serious health complications. Additionally, formula milk may lead to protein intolerance, which often results in allergies among infants. This study aims to identify the factors associated with formula feeding in infants aged 0-6 months. The study employed an analytic observational approach with a cross-sectional design, involving 55 mothers with infants aged 0-6 months. Participants were selected using accidental sampling. Data were analyzed using the Chi-square statistical test. The univariate analysis revealed that the majority of respondents (56.4%) had good knowledge of infant feeding practices, while 30.9% had a junior high school education. Most respondents (76.4%) were not employed, and 56.4% of mothers reported giving formula milk to their infants. The bivariate analysis showed a significant relationship between maternal knowledge and formula feeding practices, but no significant relationship was found between the mother's education level or employment status and the use of formula milk. Based on these findings, it is recommended that healthcare workers play a more active role in providing education, information, and motivation to mothers, helping them understand the benefits and advantages of exclusive breastfeeding. By increasing maternal knowledge and addressing misconceptions, healthcare workers can contribute to improving exclusive breastfeeding rates and reducing the unnecessary use of formula feeding.